(untitled) (Journal of the College of Basic Education, 2022)
The present research aims to prepare a group football training exercises that fit the capabilities of the research sample to identify the impact of the group training exercises in developing some of the skills of the youth football skills, and used in the research experimental method and the method of equal groups with pre- and post-test to suit its nature, The research community represented a group of (12) athletes from Qalaat Sukkar youth club. The researcher chose the research sample in the deliberate way and the ages of (16-19) years to represent the experimental group, The survey was conducted on them. The researchers have prepared a group of composite exercises lasted for 10 weeks and two units for the first two weeks and three units for the rest of the training units in a week, and after the implementation of the training program or group exercises and conducting pre- and post-tests the researchers came to the conclusion that the use of group training exercises helped in Developing some skills for football players.